HUBUNGAN HOLISTIC HEALTH ASSESMENT DENGAN KUALITAS HIDUP PASIEN HEMODIALISA - imaru diani; efroliza efroliza (IKesT Muhammadiyah Palembang, 2023)
Introduction. Kidney failure is a case that continues to increase globally. Kidney failure patients require renal replacement therapy as an effort to improve the patient's condition. Hemodialysis therapy is an option that is often used as renal replacement therapy in patients with end-stage renal failure. Hemodialysis therapy not only provides a level of life expectancy for patients, but on the other hand it can have an impact on changing the patient's health condition holistically and can affect the patient's quality of life. Objective. The study aims to determine the relationship of holistic health assessment to the quality of life of hemodialysis patients at Palembang Hospital. Methodology. The study used a cross sectional design with a total sampling method of 51 respondents. The instruments used in this study were the Dialysis Symptom Index (DSI) and DF 36. Analysis of the results of the data used the Pearson test. Results. Based on the results of the SPSS analysis, the value of r = -0.428 and pvalue 0.002 (p <0.05) was obtained, which means that there is a relationship between holistic health assessment and quality of life in hemodialysis patients at Palembang Hospital. Discussion. Based on the results of the study, there is a negative relationship between holistic health assessment and patient's quality of life. This means that patients undergoing hemodialysis tend to experience health problems both physically and psychologically which can have an impact on reducing the patient's quality of life.